Atypical presentation of Middle East respiratory syndrome coronavirus in a Lebanese patient returning from Saudi Arabia - Saeed El Zein; Jinane Khraibani; Nada Zahreddine; Rami Mahfouz; Nada Ghosn; Souha S Kanj (Journal of Infection in Developing Countries)
Around 2090 confirmed cases of Middle East Respiratory Syndrome Coronavirus (MERS-CoV) from 27 countries have been reported to the World Health Organization (WHO) between September 2012 and October 2017, the majority of whom occurring in countries in the Arabian Peninsula, mainly in Saudi Arabia. MERS- CoV can have atypical and misleading presentations resulting in delays in diagnosis and is associated with a high mortality rate especially in elderly patients with multiple comorbidities. Herein, we present the first case of confirmed MERS-CoV infection diagnosed at the American University of Beirut Medical Center (AUBMC) - Lebanon in June 2017 presenting without any respiratory symptoms. This is the second confirmed case of MERS-CoV infection in Lebanon since 2014. The first case presented with a febrile respiratory infection with persistent symptoms despite antibiotic treatment.